AlGaN layer structures for deep UV emitters on laterally overgrown AlN/sapphire templates. Issue 3 (18th December 2012) - Knauer, A.; Kueller, V.; Zeimer, U.; Weyers, M.; Reich, C.; Kneissl, M.
Abstract The crystalline perfection of n‐type AlxGa1 − xN layers with Al content higher than x > 0.4 on epitaxial laterally overgrown AlN was investigated by high resolution X‐ray diffraction, photoluminescence (PL), cathodoluminescence (CL) and resistivity mapping. The critical layer thickness of AlGaN is drastically increased compared to planar AlN/sapphire templates. CL mapping reveals compositional variations caused by different Ga incorporation during growth over steps resulting from step bunching of the AlN. With increasing Al content the homogeneity is improved. N‐type conductivity was achieved for AlGaN with Al content of up to 82%. Temperature dependent PL measurements of AlGaN/AlN multi quantum wells (MQW) emitting at 230 nm show that the internal quantum efficiency improves by a factor of about two for MQWs on defect reduced laterally overgrown AlN compared to planar AlN/sapphire templates. The data show the usefulness of defect reduced AlN templates as quasi‐substrates for AlGaN layer structures with high Al content that can be employed in light emitting diodes emitting in the deep ultraviolet.